Natural science from the worldview of the Qur’an integration model: sharing of experience in the production of textbooks - Hassan, Nur Jannah (2019)
The presentation shares the Model of Integration devised and applied in the production of the 3-voume reference textbook, Natural Science from the Worldview of the Qur'an: An Introduction. It also shares the experiences that the author went through at the different stages of the project, from the field research to the trial efforts of finding the right nuance and approach to writing the textbooks, and the challenges faced along the way.